2022
DOI: 10.3389/fonc.2022.845009
|View full text |Cite
|
Sign up to set email alerts
|

The Long Non-Coding RNA HOXC-AS3 Promotes Glioma Progression by Sponging miR-216 to Regulate F11R Expression

Abstract: HOXC cluster antisense RNA 3 (HOXC-AS3) is a long noncoding RNA (lncRNA) that plays a crucial role in various tumors; nevertheless, its role in glioma and its mechanism have not been completely elucidated. In this research, we discovered that HOXC-AS3 was over-expression in glioma cells and tissues and was associated with prognosis. Next, we determined that HOXC-AS3 targeted miR-216 as a sponge and that the F11 receptor (F11R) was the target of miR-216 by online databases analysis, qRT–PCR, and luciferase repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 50 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…Next, according to the intersection of bilateral eyes and ears 2 mm to the right, the skull of nude mice was drilled by using a dental drill. The cell suspensions of U251‐GFP‐Luc (1 × 10 6 cells) were absorbed by a sterilized microsampler and then fixed on the stereotaxic instrument 22,23 . The needle was inserted along the borehole (about 3 mm), and the stereotaxic instrument was started to slowly inject the cell suspension after receding 1 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, according to the intersection of bilateral eyes and ears 2 mm to the right, the skull of nude mice was drilled by using a dental drill. The cell suspensions of U251‐GFP‐Luc (1 × 10 6 cells) were absorbed by a sterilized microsampler and then fixed on the stereotaxic instrument 22,23 . The needle was inserted along the borehole (about 3 mm), and the stereotaxic instrument was started to slowly inject the cell suspension after receding 1 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The cell suspensions of U251‐GFP‐Luc (1 × 10 6 cells) were absorbed by a sterilized microsampler and then fixed on the stereotaxic instrument. 22 , 23 The needle was inserted along the borehole (about 3 mm), and the stereotaxic instrument was started to slowly inject the cell suspension after receding 1 mm. Post the injection, the drill hole was closed with bone wax, followed by the suturing of skin incision, and the sterilization of wound surface.…”
Section: Methodsmentioning
confidence: 99%
“… 16 Additionally, the expression level of HOXC-AS3 was found to be inversely correlated with the prognosis of glioma patients. 16 Furthermore, HOXC-AS3 could facilitate glioma cell proliferation, migration, invasion, and tumor growth by upregulating F11R expression through sponging miR-216 16 or participate in HOXB13-induced glioblastomas cell proliferation, migration, and invasion. 21 …”
Section: The Role Of Hoxc‑as3 and Its Regulatory Mechanisms In Variou...mentioning
confidence: 98%
“…HOXC-AS3 displayed different prognostic significance in different cancer types. In most of the reported tumors, including gastric cancer, 17 glioma, 16 breast cancer, 11 , 19 , 20 cervical cancer, 36 hepatocellular carcinoma, 15 HOXC-AS3 overexpression tends to predict poor prognosis, whereas in colorectal cancer (CRC), 12 high expression of HOXC-AS3 indicates good prognosis.…”
Section: Expression Of Hoxc-as3 and Its Clinical Value As A Novel Bio...mentioning
confidence: 99%
“…In GBM, the homeotic box family gene HOXB13 promoted the proliferation, migration and invasiveness of tumour cells through transcriptional upregulation of HOXC-AS3 [ 22 ]. Another study reported that HOXC-AS3 promoted glioma progression by activating miR-216, which regulated F11R expression [ 23 ]. However, the potential mechanism by which HOXC-AS3 regulates the lipid metabolism of macrophages in the GIME has not been reported previously.…”
Section: Introductionmentioning
confidence: 99%